A Branding Strategy For Audience Enhacement - Sovianti, Rina (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to investigate the direct impact of brand experience on brand image, satisfaction, and brand image in the setting of shopping center visitors. The study's participants were 20-year-old or older visitors to shopping centers or malls. A purposive sampling strategy was used to choose 235 respondents for the study. PLS-SEM is used to examine the instrument's validity and reliability, as well as the study hypotheses. Hypothesis testing revealed that brand pleasure mediates the association between brand experience and brand image. In addition, brand trust mediates the link between brand experience and brand image. Theoretically, this study helps to our knowledge of how these components interact to shape brand image. Practically, the results of this study may be utilized to develop tactics for increasing visitor loyalty to retail centers or malls